Заглиблені об’єкти з поселення Тростянчик - Рудь, В.С. (Археологія, 2016)
У статті подано результати польових досліджень трьох заглиблених об’єктів, досліджених на поселенні трипільської культури Тростянчик. Викладено попередні інтерпретації щодо використання масивних глиняних виробів, знайдених в ямі 1. In 2015, three pits were excavated at the Trypillian settlement Trostianchyk. They have shown a variety of forms and fillings of sunk objects. Massive clay products of two types were found in the pit No 1: truncated-pyramidal and discal ones. If the latter are comparatively often found at the settlements, the former are absolutely unique for the Cucuteni-Trypillian culture. In comparison with some ethnographic materials, it is probable that a set of these products was used in the construction of a potter’s kiln. The pit No 2 was completely filled with burnt clay. An inverted grinding stone was found close to the bottom of the pit. In the pit No 3, three copper objects were found together with various household rubbish (sherds, animal bones, plaster, tools, and figurines). Besides the publication of the objects, the article includes two appendixes: spectral analysis of metal finds and palaeoethnobotanic attributions. В 2015 г. на трипольском поселении Тростянчик было раскопано три ямы, обнаружено разнообразие форм и заполнения углубленных объектов. В яме 1 найдено массивные глиняные изделия двух типов: срезано-пирамидальной и дисковидной формы. Если последние сравнительно часто встречаются на поселениях, то первые являются абсолютно уникальными для Кукутень-Триполья. При сопоставлении с некоторыми этнографическими материалами, комплекс этих изделий мог использоваться в конструкции печи для обжига керамики. Яма 2 полностью заполнена обмазкой, в ее придонной части находилась перевернутая зернотерка. В яме 3 рядом с разнообразным бытовым мусором (фрагменты посуды, кости животных, обмазка, орудия труда и пластика) найдено три медных изделия. Кроме публикации объектов, статья снабжена двумя приложениями: спектральным анализом металла и палеоэтноботаническими определениями.